Restoring fiscal sanity 2007 the health spending challenge - Antos, Joseph R.; Rivlin, Alice M.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Authors suggest reforms in federal programs that have the potential to reduce the growth of spending for the entire health system, increase the efficiency and effectiveness of care provided, and enhance health outcomes and stress the need for innovative approaches and cooperation between the private and public sectors"--Provided by publisher.
Overview -- Rising health care spending--federal and national / Joseph R. Antos and Alice M. Rivlin -- Strategies for slowing the growth of health spending / Joseph R. Antos and Alice M. Rivlin -- The challenge of Medicare / Gail R. Wilensky -- The role of Medicaid / Alan R. Weil and Louis F. Rossiter -- Leveraging other federal health systems / Susan D. Hosek -- Private payer roles in moving to more efficient health spending / Paul B. Ginsburg -- Cost containment and the politics of health care reform / Judith Feder and Donald W. Moran -- Building public support for slowing the growth of health care spending / Stuart M. Butler.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Health care reform -- Economic aspects -- United States; Medical care -- United States -- Cost control; Medical care, Cost of -- United States; Medical economics -- United States; Electronic books